Identification in dynamic binary choice models - Gary Chamberlain (Centre for Microdata Methods and Practice (cemmap), 2023)
This paper studies identification in a binary choice panel data model with choice probabilities depending on a lagged outcome, additional observed regressors and an unobserved unit-specific effect. It is shown that with two consecutive periods of data identification is not possible (in a neighborhood of zero), even in the logistic case.
Keywords: C23; C33; 330; Panel Data; Binary Choice; Feedback; Identification